BRICS and beyond : executive lessons on emerging markets - Jones, Stephanie, 1957- (Chichester, West Sussex : Wiley, 2012)
With its wide range of current case illustrations and concise summaries, this is a new-generation text that will welcome today & rsquo;s MBA student to the wider world of 21st century international business. & ldquo; & hellip;this book is needed not only because it looks at business from the BRICS points of view; it also looks at business from the point of view of tomorrow & rsquo;s business leaders, and the challenges that they will have to cope with. & rdquo; & mdash;Professor Jonathan Gosling, Centre for Leadership Studies, and co-founder, The One-Planet MBA, the University of Exeter, UK & ldquo; & he.
Preface / by Prof Dr. Wim Naude -- About the author -- Introduction -- Doing business in emerging markets : risks, opportunities and practice -- First section: risks -- Country risk -- Politics and business in emerging markets -- Corporate social responsibility -- Ethics, transparency, and governance in emerging markets -- Business culture -- Cross-cultural management and people in emerging markets -- Second section: opportunities -- Marketing -- Implementing marketing ideas into and from emerging markets -- Entrepreneurship and innovation -- Technology, innovation, and new business ventures in emerging markets -- Third section: practice -- Strategy and operations -- Changing business strategies and operations in emerging markets -- Strategic alliances -- Western business and emerging market business : working together -- Lessons for global business -- What we can learn from the brics and beyond -- Reading list -- Glossary -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: International business enterprises -- Developing countries; Social responsibility of business -- Developing countries; Diversity in the workplace -- Developing countries; Industrial management -- Developing countries; BUSINESS & ECONOMICS -- International -- General; Diversity in the workplace; Industrial management; International business enterprises; International economic relations; Social responsibility of business; BRIC countries -- Foreign economic relations; BRIC countries; Developing countries; Electronic books; Electronic books